Analisis Penggunaan E-Modul terhadap Motivasi dan Minat Belajar Siswa Kelas VII dalam Pembelajaran IPA di SMP Negeri 11 Samarinda - Paradistala, Maria Yeni; Jailani, Jailani; Akhmad, Akhmad; Maasawet, Elsje Theodora (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to measure the level and changes in motivation in grade VII students at SMP Negeri 11 Samarinda in science learning. The approach used in this study is quantitative descriptive with 34 students as samples determined through the Convenience Sampling method. The media used is a flipbook-based e-module. Three instruments were used in data collection, namely a questionnaire filled out by students, a student participation observation sheet filled out by the teacher, and multiple-choice questions assessed by the researcher. The results of the study showed that the average score of student learning motivation was 44.29 and student interest in learning was 40.47, both of which are included in the fairly high category. The results of data analysis from the three instruments showed an increase in student motivation and interest in learning, accompanied by significant positive changes. Based on these findings, the researcher concluded that the implementation of a flipbook-based e-module has a positive impact on student motivation and interest in learning.